Identification of Synthetic Cannabinoid 5F-ADB (5F-MDMB-PINACA) and Its Metabolite in Urine Sample Using Liquid Chromatography – High Resolution Mass Spectrometer (LC-HRMS) - Rieska Dwi Widayati; Tanti Tanti; Erlana Nindya Maulida; Martin Luther Silubun (The Journal of Pure and Applied Chemistry Research, 2020)
Synthetic cannabinoids are commonly known as Gorillas Tobacco, Hanomans Tobacco or Ganeshas Tobacco in Indonesia. Those products are camouflaged as a tobacco related to the number of smokers in Indonesia. The 5F-ADB (5F-MDMB-PINACA) has become an issue since 2016. It was undetectable by conventional drug testing methodology such as immunoassay method. GC-MS as a routine method analysis is not recommended also for detecting the metabolites from biological specimen with low concentration. The paper report LC-HRMS based method for identification of 5F-ADB and its metabolites in urine sample. Various of volume injections (1, 3, and 6 µL) was studied. Sample was acidified with concentrate of HCl, then undergo extraction with EXtrelut® Column NT3 prior to LC-HRMS analysis. The full method was operated for MS/dd-MS2 identification. The 5F-ADB and its ester hydrolysis metabolite, 5F-ADB metabolite 7 (C19H27FN3O3+) was detected in urine sample.